Design and theoretical analysis of the image-side telecentric zoom system using focus tunable lenses based on Gaussian brackets and lens modules. (May 2023) - Li, Jingchen; Zhang, Kun; Du, Jialin; Li, Fanxing; Yang, Fan; Yan, Wei
Highlights: This paper presents the design method of the image-side telecentric zoom system with four focus tunable lenses (FTL) and a moving aperture stop (STO) by applying gaussian brackets and lens modules. Compared to conventional mechanical zoom telecentric systems, this system greatly reduces the mechanical moving group, thus reducing the structural complexity of the system, greatly reducing mechanical vibrations and misalignments, which is a great advantage for telecentric systems where the application scenario requires high accuracy, and makes it easier to achieve control of the total length. The work we study mainly concentrate on improving gaussian brackets, establishing screening method used in solution space, using the lens module method design the telecentric zoom FTL system, and extending the lens module combination method applicable to the lens group contains an FTL. We believe that this article is suitable for publication in optics and lasers in Engineering. The design method of the telecentric zoom FTL system proposed in this paper is simple in principle, easy to understand and has excellent effectiveness when applied to the actual design process, which is an important reference for the development and research of subsequent telecentric zoom FTL systems. Abstract: For now, telecentric system and zoom system have been extensively implemented in machine vision, industrial inspection, etc. However, studies on optical systems with both telecentric and zoom functions are still rare. To improve this situation, we present the design method of the telecentric zoom system with four focus tunable lenses (FTL) and a moving aperture stop (STOP) by applying Gaussian brackets and lens modules. We first improve the Gaussian brackets to achieve the initial parameter solution of the telecentric zoom FTL system, then we introduce a selection method to find the initial structural parameters with sufficient potential for optical design. After that, we use the lens module method to design the initial structure of the optical system, we also expand the combination method of the lens modules which contains an FTL. Finally, the initial structures of a 4X image-side telecentric zoom FTL system are constructed as an example and then optimized using CODEV. As a result, we get an image-side telecentric zoom FTL system with an F/# of 4, a zoom range of 20 mm to 80 mm, an image plane size of 8 mm, and a total length of 218 mm, which performs well in telecentricity control, distortion control, and aberration correction.